2013
DOI: 10.1016/j.jacc.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Prevent Post-Operative Atrial Fibrillation by Antioxidant Reinforcement

Abstract: This safe, well-tolerated, and low-cost regimen, consisting of n-3 polyunsaturated fatty acids plus vitamins C and E supplementation, favorably affected post-operative atrial fibrillation, increased antioxidant potential, and attenuated oxidative stress and inflammation. (Prevention of Post-Operative Atrial Fibrillation: Pathophysiological Characterization of a Pharmacological Intervention Based on a Novel Model of Nonhypoxic Pre-Conditioning; ISRCTN45347268).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 37 publications
2
89
1
5
Order By: Relevance
“…3 studies were excluded, as they administered vitC combined with other treatments under evaluation. [24][25][26] 2 studies in clinical trial registries were excluded for not posting results, and authors were unavailable for comment. 27,28 1 study in a Russian language journal was excluded, as the journal was unavailable in electronic or print form, and the journal did not make its articles available outside the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…3 studies were excluded, as they administered vitC combined with other treatments under evaluation. [24][25][26] 2 studies in clinical trial registries were excluded for not posting results, and authors were unavailable for comment. 27,28 1 study in a Russian language journal was excluded, as the journal was unavailable in electronic or print form, and the journal did not make its articles available outside the Russian Federation.…”
Section: Resultsmentioning
confidence: 99%
“…It is quite difficult, if not impossible, to obtain reliable recordings of cellular events in intact human hearts at the onset of AF [33]. Human clinical studies demonstrated the occurrence of new onset acute oxidative AF by showing that inhalation of pro-oxidant particulate matters promotes acute AF in patients with cardiac disease [34] and that such effects can be minimized by antioxidant therapy [35]. Genomic analyses showed that genes that were uniquely up regulated in patients with no POAF were mostly supported by reduction reactions suggesting that the overall redox balance favors anti-oxidant state in these patients resistant to POAF [3].…”
Section: Discussionmentioning
confidence: 99%
“…Inne metody leczenia również oceniano w małych próbach klinicznych generujących nowe hipotezy badawcze, ale nie wykazano jednoznacznie ich korzystnych efektów. Do ocenianych metod należało stosowanie magnezu [925,935,936], wielonienasyconych kwasów tłuszczowych z grupy omega-3 [937][938][939][940][941][942][943][944][945], kolchicyny [946] i glikokortykosteroidów [947,948], a także wycięcie tylnej części osierdzia [949]. Pooperacyjna stymulacja dwuprzedsionkowa narzuconym szybkim rytmem (overdrive) nie znalazła powszechnego zastosowania mimo pewnych danych wskazujących na jej profilaktyczny efekt [925,950].…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified